If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -2n = n + 64 Reorder the terms: 2 + -2n = 64 + n Solving 2 + -2n = 64 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 2 + -2n + -1n = 64 + n + -1n Combine like terms: -2n + -1n = -3n 2 + -3n = 64 + n + -1n Combine like terms: n + -1n = 0 2 + -3n = 64 + 0 2 + -3n = 64 Add '-2' to each side of the equation. 2 + -2 + -3n = 64 + -2 Combine like terms: 2 + -2 = 0 0 + -3n = 64 + -2 -3n = 64 + -2 Combine like terms: 64 + -2 = 62 -3n = 62 Divide each side by '-3'. n = -20.66666667 Simplifying n = -20.66666667
| 0.33=6 | | 2x^2-10x=6 | | 10x-3=-17 | | (3k-7)/(5)=16 | | 49+1-4c=39c-2 | | 2k+k+4= | | [t+5]+3=12 | | 7-2x=0 | | 6x+8=4x+50 | | 3x+8=8+2x+x | | 729=x^3 | | 4(d-20)=1 | | 245=-7a | | (36-5x)+(36-5x)+4x+4x=x | | 3x+28=7(x+4)-4x | | 2(6+3)=18-3(16-3d) | | 6+12=16 | | x+17=36-x | | x=20-0.5y | | 5=1-2n+5 | | 4(d-5)=1 | | 5m-14=8m+4 | | 2.5x-(-8.2)=26.7 | | -8n+4(1+5)=6n-14 | | -11(x+9)=99 | | 6x^4*3x^4= | | y=-0.80(55)+136 | | 4.3*p=28.81 | | 5n-9=71 | | 5(x+4)=75 | | 6y-7=10y+25 | | y=-0.80(45)+136 |